News from Moscow : Soviet journalism and the limits of postwar reform - Huxtable, Simon, 1980- 1980- (Oxford University Press, 2022)
"News from Moscow: Journalism and the Fate of the Thaw Project is a history of the post-war Soviet press that takes readers from the tense ideological climate of the late Stalin era to the comparative freedom of the Thaw. Through a case study of one of the country's most innovative and popular titles, the youth daily Komsomol'skaia pravda, the book shows how journalists attempted to remake the Soviet newspaper after Stalin's death, but details the many obstacles they faced along the way. The book argues that Thaw journalism was characterised by an unresolvable tension between innovation and conservativism: the more journalists tried to devise new forms to attract readers, the more officials grew anxious about the potentially disruptive consequences of reform. Taking readers from the gloomy climate of late Stalinism to the invasion of Czechoslovakia in 1968, the book's six chapters offer examples of journalists attempts to innovate, from its advocacy for person-centred pedagogy in the late Stalin and Thaw periods, to the creation of the country's first polling institute and its support for Brezhnev's technocratic reforms in the 1960s. Drawing on a range of unseen internal documents, including transcripts of private editorial meetings, the book takes readers into the Soviet newsroom for the first time, and details the conversations - with colleagues, functionaries and readers - that characterised journalists' daily work, and the conflicts with officials that came to characterise the Thaw project"